Dengue and Chikungunya virus co-infection in major metropolitan cities of provinces of Punjab and Khyber Pakhtunkhwa: A multi-center study. - Faiz Ahmed Raza; Hasnain Javed; Muhammad Mujeeb Khan; Obaid Ullah; Areeba Fatima; Muhammad Zaheer; Saima Mohsin; Shahida Hasnain; Ruqyya Khalid; Arslan Ahmed Salam (Public Library of Science (PLoS), 2021)
Dengue has become endemic in Pakistan with annual recurrence. A sudden increase in the dengue cases was reported from Rawalpindi in 2016, while an outbreak occurred for the first time in Peshawar in 2017. Therefore, a multi-center study was carried out to determine the circulating dengue virus (DENV) serotypes and Chikungunya virus (CHIKV) co-infection in Lahore, Rawalpindi, and Peshawar cities in 2016-18. A hospital-based cross-sectional study was carried out in Lahore and Rawalpindi in 2016-18, while a community-based study was carried out in Peshawar in 2017. The study participants were tested for dengue NS1 antigen using an immunochromatographic device while anti-dengue IgM/IgG antibodies were detected by indirect ELISA. All NS1 positive samples were used for DENV serotyping using multiplex real-time PCR assay. Additionally, dengue samples were tested for CHIKV co-infection using IgM/IgG ELISA. A total of 6291 samples were collected among which 8.11% were NS1 positive while 2.5% were PCR positive. DENV-2 was the most common serotype (75.5%) detected, followed by DENV-1 in 16.1%, DENV-3 in 3.9% and DENV-4 in 0.7% while DENV-1 and DENV-4 concurrent infections were detected in 3.9% samples. DENV-1 was the predominant serotype (62.5%) detected from Lahore and Rawalpindi, while DENV-2 was the only serotype detected from Peshawar. Comorbidities resulted in a significant increase (p-value<0.001) in the duration of hospital stay of the patients. Type 2 diabetes mellitus substantially (p-value = 0.004) contributed to the severity of the disease. Among a total of 590 dengue positive samples, 11.8% were also positive for CHIKV co-infection. Co-circulation of multiple DENV serotypes and CHIKV infection in Pakistan is a worrisome situation demanding the urgent attention of the public health experts to strengthen vector surveillance.